Vascular neoplasia masquerading as cellulitis and persistent hemorrhagic pericardial effusion - Sharan Thangaraju; Jay Relan; Aditi Sinha; Sudheer Kumar Arava; Neena Khanna; Sreenivasa Narayana Raju (Wolters Kluwer Medknow Publications, 2022)
Tufted angioma and kaposiform hemangioendothelioma are considered to represent two ends of the spectrum of benign vascular neoplasms that predominantly present during infancy or early childhood. We report a rare case of a 5-month-old infant with complicated vascular neoplasm involving the pericardial cavity and skin over cervical region, masquerading as infective pericarditis with cellulitis. The patient responded dramatically to therapy with oral prednisolone and sirolimus, with a significant reduction of size of skin lesions and complete resolution of pericardial effusion over 8 weeks. The report also highlights the importance of a multidisciplinary team in managing such complicated cases.